Point Mutations in the folP Gene Partly Explain Sulfonamide Resistance of Streptococcus mutans - W. Buwembo; S. Aery; C. M. Rwenyonyi; G. Swedberg; F. Kironde (International Journal of Microbiology)
Cotrimoxazole inhibits dhfr and dhps and reportedly selects for drug resistance in pathogens. Here, Streptococcus mutans isolates were obtained from saliva of HIV/AIDS patients taking cotrimoxazole prophylaxis in Uganda. The isolates were tested for resistance to cotrimoxazole and their folP DNA (which encodes sulfonamide-targeted enzyme dhps) cloned in pUC19. A set of recombinant plasmids carrying different point mutations in cloned folP were separately transformed into folP-deficient Escherichia coli. Using sulfonamide-containing media, we assessed the growth of folP-deficient bacteria harbouring plasmids with differing folP point mutations. Interestingly, cloned folP with three mutations (A37V, N172D, R193Q) derived from Streptococcus mutans 8 conferred substantial resistance against sulfonamide to folP-deficient bacteria. Indeed, change of any of the three residues (A37V, N172D, and R193Q) in plasmid-encoded folP diminished the bacterial resistance to sulfonamide while removal of all three mutations abolished the resistance. In contrast, plasmids carrying four other mutations (A46V, E80K, Q122H, and S146G) in folP did not similarly confer any sulfonamide resistance to folP-knockout bacteria. Nevertheless, sulfonamide resistance (MIC = 50 μM) of folP-knockout bacteria transformed with plasmid-encoded folP was much less than the resistance (MIC = 4 mM) expressed by chromosomally-encoded folP. Therefore, folP point mutations only partially explain bacterial resistance to sulfonamide.